2022
DOI: 10.1017/s0033291721004761
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk, familial liability and stress reactivity in psychosis: an experience sampling study

Abstract: Background There is evidence for a polygenic contribution to psychosis. One targetable mechanism through which polygenic variation may impact on individuals and interact with the social environment is stress sensitization, characterized by elevated reactivity to minor stressors in daily life. The current study aimed to investigate whether stress reactivity is modified by polygenic risk score for schizophrenia (PRS) in cases with enduring non-affective psychotic disorder, first-degree relatives of cases, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…That being said, some youth in our study who experienced high levels of conflict, rigidity, and low warmth may conceivably be experiencing FE that overlaps with maltreatment, which has been shown to have detrimental effects on health over the life course (Lippard & Nemeroff, 2020;Palmier-Claus et al, 2016;Stapp, Williams et al, 2020). Taken together, a small but converging body of evidence is consistent with the liability threshold model, in which lower genetic burden, in the presence of environmental stress (i.e., multifactorial), is associated with increased mood and psychotic disorder liability (Schick et al, 2022;Tonini et al, 2022). These findings are also somewhat consistent with studies demonstrating the importance of early adversity and parentchild relationship quality on differential stress responsivity and mood (Rudolph et al, 2020;Shakiba et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…That being said, some youth in our study who experienced high levels of conflict, rigidity, and low warmth may conceivably be experiencing FE that overlaps with maltreatment, which has been shown to have detrimental effects on health over the life course (Lippard & Nemeroff, 2020;Palmier-Claus et al, 2016;Stapp, Williams et al, 2020). Taken together, a small but converging body of evidence is consistent with the liability threshold model, in which lower genetic burden, in the presence of environmental stress (i.e., multifactorial), is associated with increased mood and psychotic disorder liability (Schick et al, 2022;Tonini et al, 2022). These findings are also somewhat consistent with studies demonstrating the importance of early adversity and parentchild relationship quality on differential stress responsivity and mood (Rudolph et al, 2020;Shakiba et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…In line with this, individuals with a high risk of psychosis show increased distress-induced psychotic reactivity (i.e., behavioral sensitization (Collip et al, 2008)) compared to healthy controls (Klippel et al, 2017;Reininghaus et al, 2016). Additionally, a polygenic risk score for schizophrenia (PRS) predicted a stronger association between stress and psychotic experiences in healthy controls (Schick et al, 2022). However, in unaffected siblings of individuals diagnosed with schizophrenia, a higher PRS was related to reduced psychotic reactivity.…”
Section: Introductionmentioning
confidence: 75%
“…( 2016 ) found similar results: the PRS-SZ and childhood trauma history predicted both psychosis status, without interaction between these factors. To our knowledge, two other studies have looked for such interactions, that found a significant GxE interaction between the PRS-SZ and childhood trauma (Pries et al ., 2020 b ; Schick et al ., 2022 ). Another study using the PRS-SZ and conducted in adults looked for interaction with other environmental factors, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies assessed the interaction between PRS-SZ and childhood trauma, but only one reported a significant interaction (Pries et al ., 2020 b ), whereas the other showed an independent (additive) effects of the PRS-SZ and the trauma without significant interaction (Trotta et al ., 2016 ). A recent study assessing the associations between momentary stress and subclinical psychotic symptoms showed that higher levels of PRS-SZ were associated with a higher intensity of symptoms after a momentary stress among controls (Schick et al ., 2022 ). In the fourth study, the authors assessed the interaction between PRS-SZ and smoking status, but did not show significant association (García-González et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%